Jazz aesthetics in the French Caribbean novel - Panton, Diana A. (My University, 2000)
This thesis examines the use of jazz as theme, structure and metaphor in French Caribbean texts. Daniel Maximin's L'lsolé Soleil, Stanley Péan's Zombi Blues, and Ernest Pépin's Tambour-Babel integrate jazz aesthetics such as improvisation, call-and-response, quoting, and rhythm to structure their novels and highlight the aural/oral quality of their texts. On a thematic level, these authors show the effects of the Plantation system on artistic modes of production and the treatment of the artist in society. Metaphorically, jazz in the novels suggests resistance and cultural marronnage, as well as spiritual and artistic freedom. The syncretic origins of jazz that blend African and European musical elements make this musical genre an ideal vehicle to express the hybrid quality of French Caribbean literature whose open-endedness and continuous evolution resist simplification and standardization. Jazz musicians with distinctive voices such as Miles Davis, Charlie Parker and Coleman Hawkins have done for jazz what Daniel Maximin, Stanley Péan and Ernest Pépin are attempting to accomplish for the cultural inheritance of the French Caribbean -- affirm their existence through artistic expression.
Keywords: French and Francophone Language and Literature; French and Francophone Language and Literature